2001
DOI: 10.1002/jmri.1207
|View full text |Cite
|
Sign up to set email alerts
|

Method for quantitative mapping of dynamic MRI contrast agent uptake in human tumors

Abstract: A method is presented for the acquisition and analysis of dynamic contrast-enhanced (DCE) MRI data, focused on the characterization of tumors in humans. Gadolinium (Gd) contrast was administered by bolus injection, and its effect was monitored in time by fast T1-weighted MRI. A simple algorithm was developed for automatic extraction of the arterial input function (AIF) from the DCE-MRI data. This AIF was used in the pixelwise pharmacokinetic determination of physiological vascular parameters in normal and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
158
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 37 publications
0
158
3
1
Order By: Relevance
“…Some sources of registration error are individual variance in patient brain geometry and the mass effect. Radiation necrosis resulting from treatment, which may appear similar to active tumor on the image, can further complicate MR image interpretation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some sources of registration error are individual variance in patient brain geometry and the mass effect. Radiation necrosis resulting from treatment, which may appear similar to active tumor on the image, can further complicate MR image interpretation [22].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the use of an individually measured AIF will increase the accuracy with which parameterizations may be obtained relative to the use of an assumed AIF (16,17). It has also been suggested that measuring an AIF aides the reproducibility of parameter estimation by accounting for day-to-day variation in contrast agent (CA) administration and physiological factors that may affect CA circulation (17). However, measurement of an AIF is itself subject to errors, which can potentially lead to degraded parameter accuracy and reproducibility.…”
mentioning
confidence: 99%
“…In this case, the use of the proposed linear fitting may lead to fitting deviations. However, according to the reported values in the literature, fortunately very few k ep values over 5/min have been reported for different kinds of tumors and normal tissues (21,(25)(26)(27)(28)(29), indicating the feasibility and practicability of using this mapping method for different DCE-MRI applications. As seen in Table 1, the narrower k ep range to be fit, the better linearity is found between TSF and k ep .…”
Section: Discussionmentioning
confidence: 99%
“…Simply put, pixels from blood vessels were identified if the maximum enhancement of one pixel was greater than the average plus two times the standard deviation (SD) of the maximum enhancement of all pixels in this slice. The arteries were separated from veins according to the time delay to the maximum signal intensity (21). For convenience, the TICs for arteries were referenced as AIF.…”
Section: Data Processing and Analysismentioning
confidence: 99%